Cover Feature: Radical Complexes of Nickel(II)/Copper(II) and Redox Non‐innocent MB‐DIPY Ligands: Unusual Stability and Strong Near‐Infrared Absorption at λmax ∼1300 nm (Chem. Eur. J. 41/2022). Issue 41 (4th July 2022) - Zatsikha, Yuriy V.; Shamova, Liliya I.; Shepit, Michael; Berry, Steven M.; Thomas, Fabrice; Herbert, David E.; van Lierop, Johan; Nemykin, Victor N.
Abstract : The preparation of radicals with intense and redox‐switchable absorption beyond 1000 nm is a long‐standing challenge in the chemistry of functional dyes. We now report a series of unprecedented stable neutral nickel(II) and copper(II) complexes of "Manitoba‐dipyrromethenes" (MB‐DIPYs) in which the organic chromophore is present in the anion–radical state. The new stable radicals have an intense absorption at λ max ∼1300 nm and can be either oxidized to a regular [M II (MB‐DIPY)] + (M = Cu or Ni) or reduced to [M II (MB‐DIPY)] − compounds. More information can be found in the Research Article by F. Thomas, J. van Lierop, V. N. Nemykin, and co‐workers (DOI: 10.1002/chem.202201181 ).